RETRACTED ARTICLE: Degradable poly-L-lysine-modified PLGA cell microcarriers with excellent antibacterial and osteogenic activity - Hanyang Zhang; Jianhang Jiao; Hui Jin (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We, the Editors, Authors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Hanyang Zhang, Jianhang Jiao & Hui Jin (2019) Degradable poly-L-lysine-modified PLGA cell microcarriers with excellent antibacterial and osteogenic activity. Artificial Cells, Nanomedicine, and Biotechnology, 47:1, 2391–2404, DOI: 10.1080/21691401.2019.1623230Since publication, the authors continued their study and found that the original experimental results were unverifiable. The authors checked their data and confirmed there are fundamental errors present. Therefore, they have agreed to the retraction of this article. The authors apologise for this oversight.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.